Povidone-iodine versus normal saline solution in preoperative vaginal cleansing before office hysteroscopy: a randomized controlled trial - Abbas, Ahmed M.; Shaltout, Asmaa S.; Ali, Shymaa S.; Michael, Armia; Altraigey, Ahmed; Abdelfatah, Laila E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysteroscopy is well-thought-out the gold standard for assessing the uterine cavity, and now can be done as an office process due to enhanced endoscopic advances with no need to in-patient admission. Objective of the present study was to compare the difference in the rate of postoperative vaginal irritation symptoms and postoperative infections after using povidone iodine (PI) and normal saline (NS) solution in vaginal cleaning before outpatient office hysteroscopy (OH). Methods: Women attended to the hospital for diagnostic OH were included for present study. Eligible women were randomly allocated in a 1:1 ratio to two groups. Group I "PI group" women exposed to PI for vaginal cleansing before hysteroscopy, and group II "NS group” women exposed to the NS solution for vaginal cleansing. The primary outcome of the study was to compare the difference in the rate of postoperative vaginal irritation symptoms and postoperative infections in both groups. Results: The mean age of the study participants was 34.26±4.14 years for NS group compared to 35.22±4.01 years for PI group (p=0.652). The PI group reported higher rate of vaginal irritation than NS group with no statistically significant difference between the two groups (p=0.179). Both groups were similar in postoperative fever, urinary tract infection and vaginitis (p>0.05). Conclusions: This study concluded that preoperative vaginal disinfection at the time of OH with a NS solution is less frequently causing postoperative vaginal irritation symptoms. Additionally, it is as effective as the usual agent (PI) in preventing postoperative infections.